Who Should Raise Good Citizens and How? - Vačun, Maja (Analiza: časopis za kritično misel, 2025)
This paper reflects on the type of citizen required by a liberal-democratic society and the role of the educational system in shaping »good« citizens. Good citizenship goes beyond civic knowledge and skills. It is grounded in civic virtues (responsibility, justice, solidarity, willingness to cooperate, and concern for the common good), which include motivation and are expressed through actions. The educational system plays a crucial role in developing these qualities, but it is only one of the factors that influence young people. Equally important are the school’s connections with other social spheres and a holistic approach to civic education. An analysis of the current curriculum for the subject Civic and Homeland Culture and Ethics shows that it places greater emphasis on civic knowledge than on civic skills and virtues. The international ICCS 2022 study highlights the weak performance of Slovenian primary school students in civic knowledge, their attitudes toward key social issues, their limited participation in school and other contexts, as well as their expressed willingness to engage in the future.